2020
DOI: 10.1016/j.ijbiomac.2020.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the regulation of glucose tolerance in a β-glucosidase from Halothermothrix orenii by active site pocket engineering and computational analysis

Abstract: Elucidating the regulation of glucose tolerance through the interaction between the reaction product and 2 active site pocket residues of a β-glucosidase from Halothermothrix orenii

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…2). A comparison of the surface structures (Fig 3) showed that the active sites of Pf Bgl3A and Pf Bgl3B are open and shallow, whereas that of Pf Bgl1A is deep, narrow and tunnel-like consistent with reports on active site configuration for GH1 β-glucosidases (26, 2831). This active site conformation is thought to improve the glucose tolerance of GH1 proteins by preventing the direct access of glucose to the active site (32).…”
Section: Resultssupporting
confidence: 85%
“…2). A comparison of the surface structures (Fig 3) showed that the active sites of Pf Bgl3A and Pf Bgl3B are open and shallow, whereas that of Pf Bgl1A is deep, narrow and tunnel-like consistent with reports on active site configuration for GH1 β-glucosidases (26, 2831). This active site conformation is thought to improve the glucose tolerance of GH1 proteins by preventing the direct access of glucose to the active site (32).…”
Section: Resultssupporting
confidence: 85%
“…Experimentally, this hypothesis could be investigated by controlling the enzyme orientation on the surface, ensuring that the entrance to the catalytic site remains accessible after the enzyme immobilization, and monitoring the catalytic activity. One should also note that in the case of βGA, the broad size of the catalytic site, , which is located at the entrance of the central β-barrel, and its structural stability ensure that it remains open at all times. However, many proteins comprise a buried active site that is connected to the surface through internal tunnels and cavities (like globins or hydrogenases).…”
Section: Discussionmentioning
confidence: 99%
“…Our group recently reported the stimulation of a β-glucosidase in the presence of glucose but without transglycosylation. The β-glucosidase from Halothermothrix orenii is stimulated up to 0.5 M glucose due to the increased access of the substrate with the increase in active site pocket structural flexibility . The activation of β-glucosidases in the presence of glucose could be due to the simple competition between the glucose and nonproductive binding of substrate molecules at additional sites during enzymatic reaction .…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, most β-glucosidases are prone to glucose inhibition, and the consequent accumulation further inhibits cellobiohydrolase and endoglucanase to result in inefficient biomass hydrolysis. Therefore, the identification of efficient β-glucosidases has been an ongoing effort. Recently, there were reports of glucose-tolerant GH1 β-glucosidase that can tolerate very high glucose concentrations. ,, Glucose tolerance has been linked to stimulatory effects by low concentration of glucose, transglycosylation, allosteric effects, , and nonproductive substrate binding . The higher glucose-tolerant enzymes thus far are all reported from the GH1 family.…”
Section: Introductionmentioning
confidence: 99%